Dampak Agrowisata Trokon terhadap Sosial Ekonomi Masyarakat Desa Cawang Lama Kecamatan Selupu Rejang Kabupaten Rejang Lebong - Melsa Agustin; Dwita Frisdinawati; Anadiya Pingki; Mira Yanuarti (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted in February 2025 to May 2025. This study aims to: 1). Based on the formulation of the problem above, the purpose of this study is to determine the Impact of Trokon Agrotourism in Cawang Lama Village, Selupu Rejang District, Rejang Lebong Regency on the Socio-Economic Conditions of the Community. The methods used in this study are descriptive analysis, multiple linear regression analysis, and T-test and F-test. The method of determining respondents in this study used purposive sampling technique. Where the sample in this study was 25 respondents. Purposive sampling technique is a sampling technique with certain considerations or criteria, such as age, gender, or occupation (Sugiyono, 2018). Based on data obtained through direct observation and interviews with 25 informants regarding the Impact of Trokon Agrotourism on the Socio-Economic Conditions of the Cawang Lama Village Community, then. More specifically, the key findings of this study are that after the presence of agrotourism, all independent variables in the model - namely income (X1), business opportunities (X2), increased environmental awareness (X3), and job creation (X4) - have a significant influence on the dependent variable (Y) of the community's socio-economics. This influence is observed both positively and negatively, indicating the complexity of the dynamics of change that occurs.